A escola e os espaços não-formais: possibilidades para o Ensino de Ciências nos anos iniciais do ensino fundamental - Rocha, Sônia Cláudia Barroso da (2008)
Whereas schools and non-formal spaces has among its objectives to enable people to acquire scientific knowledge, this study aimed assess whether experiences of visits to non-formal spaces can configure itself as a strategy for improving the Teaching of Science, and if that assessment would enable the development of teaching resources to facilitate the use of public spaces by teachers and students from public schools. To this, set up a methodological path characterized by mixed approach since, worked up with quantitative and qualitative data, constructed from the techniques of: documentary analysis, observation (naturalist and participant), semi-structured interview and application the questionnaires. This journey enabled to assess that the visits to non-formal spaces, as have been carried out by schools in the municipal network, does not constitute as a strategy for the Teaching of Science in the initial years of elementary school because they are not made with this purpose . But when the visits are intentionally designed to teach science by using available resources within the non- formal space, and are well planned, considering the preparation of students, the completion of the visit and its conclusion with the systematization of knowledge built by students, the visit allows for higher learning of the conceptual content of Natural Sciences and motivate new learning, arousing greater interest of students in science. Besides that activities developed in a non-formal space with the natural environment can enable the formation of values of protecting the environment. Thus, it is believed that this work contributes to: 1) expand the knowledge built in the Teaching of Science and 2) resignified the use of non-formal spaces of Manaus to teach science in the early years of elementary school.